A review of current issues in Industrialised Building System (IBS) for construction projects / Mohd Reeza Yusof ... [et al.] - Yusof, Mohd Reeza; Jabar2, Izatul Laili; Nawawi, Abdul Hadi; Mohd Nawi, Mohd Nasrun (UiTM Press, 2024)
In Malaysia, the concept of prefabrication is known as Industrialised Building System (IBS). In terms of cost, time, productivity, and quality, IBS is certainly beneficial based on previous local and international research. As part of Construction Industry Development Board (CIDB), CIDB's Construction 4.0 Strategic Plan 2020-2025, the Malaysian construction industry is being urged to employ innovative construction techniques. These initiatives illustrate the Malaysian government's commitment to addressing the IBS agenda. Even though numerous things have been done to enhance the IBS adoption in Malaysia, various issues have arisen to bring about delays, disputes, miscommunications, and payment issues affecting the IBS players. Thus, the primary purpose of this research is to identify current issues and assist policymakers and IBS players in mitigating those issues. The literature review was the first phase of the research, with the secondary data derived from relevant books, journals, articles, theses, dissertations, conference proceedings and reports. The second phase involved the collection of primary data, wherein the information was collected through a preliminary study. The research findings showed that IBS construction still faces challenges and issues when adopted by the industry, where four (4) out of five (5) interviewees stated that the primary integration issues are teamwork or collaboration and procurement. This paper aims to present a literature review and preliminary survey findings related to establishing pertinent integration issues and challenges.